MAShINALI OʻQITISh ALGORITMLARINI REAL SOHALARDA QOʻLLASh VA USULLARINI TAHLIL QILISh - Seitnazarov, K.K.; Sultanbaeva, A.T.; Jalgasbaeva, Sh.M. (SCIENCE and SOCIETY, 2025)
This article reviews the applications of machine learning algorithms in various real-world applications. The main types of algorithms - supervised learning, unsupervised learning, and reinforcement learning - are analyzed in practical applications, and the advantages and limitations of the algorithms are discussed, as well as the future prospects of this technology. The effectiveness of machine learning is illustrated based on research results, real-world examples, and statistical data.